2012
DOI: 10.1111/j.1872-034x.2012.00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Follow up of the 987 blood donors found with hepatitis C virus infection over 9–18 years

Abstract: Individuals with undiagnosed HCV infection need to be identified and receive medical care. They have to be motivated to merit from this health-care program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
10
0
3
Order By: Relevance
“…The results of a long‐term cohort study of HCV carriers who were found to be positive at blood donation revealed that only 1097 (32.5%) among 3377 HCV carriers who had received post‐test counselling had consulted at medical institutions for further examination, and 987 (29.2%) consulted twice or more . Among them, excluding loss‐to‐follow‐up because of transfer to other hospitals, the drop‐out rate in the 1–2 years after the initial visit was 24.3%.…”
Section: Estimate Of the Total Number Of Hepatitis Virus Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a long‐term cohort study of HCV carriers who were found to be positive at blood donation revealed that only 1097 (32.5%) among 3377 HCV carriers who had received post‐test counselling had consulted at medical institutions for further examination, and 987 (29.2%) consulted twice or more . Among them, excluding loss‐to‐follow‐up because of transfer to other hospitals, the drop‐out rate in the 1–2 years after the initial visit was 24.3%.…”
Section: Estimate Of the Total Number Of Hepatitis Virus Carriersmentioning
confidence: 99%
“…After receiving passive–active immunization, all children were tested for HBsAg at 1 month of age and then HBsAg and anti‐HBs at 6 months of age. In 2015, the above prevention guideline was modified so that all children born to pregnant women positive for HBsAg, irrespective of their HBeAg status, were given HBIG and HepB vaccine at birth simultaneously, followed by another two doses of HepB vaccine at 1 month and 6 months of age …”
Section: Prevention Of Mother‐to‐child Transmission Of Viral Hepatitis Bmentioning
confidence: 99%
“…In Japan, patients infected with HCV are getting increasingly older, and they are older than those in other countries [19, 26]. Matsuo et al [26] reported that HCC developed more frequently in blood donors in whom chronic hepatitis had been diagnosed at age >60 years than ≤59 years.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuo et al [26] reported that HCC developed more frequently in blood donors in whom chronic hepatitis had been diagnosed at age >60 years than ≤59 years. In the era of direct-acting antivirals against HCV [27, 28], our current study strongly suggests that HCV-infected patients >50 years might be treated with antivirals as soon as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Conforme evidenciado por diversos trabalhos na literatura médica, a triagem sorológica dos Bancos de Sangue possibilita a oportunidade de identificar os indivíduos assintomáticos portadores da hepatite C, que precisam de acompanhamento médico e, que de outra forma, não teriam o conhecimento da doença e não seriam encaminhados para receber a assistência necessária 28,48,49,57,61 . Além da possibilidade de reconhecimento precoce da hepatite C, o diagnóstico durante a doação de sangue, seguido por um programa de saúde com acompanhamento regular destes pacientes e com a indicação de tratamento no momento adequado, está associado a melhores desfechos clínicos e melhores resultados do tratamento antiviral, como mostrado no trabalho publicado por Matsuo, em que mais de 900 doadores de sangue foram seguidos prospectivamente e tiveram seus desfechos analisados 58 .…”
Section:  Biópsias Hepáticasunclassified